Shock Index-C: An Updated and Simple Risk-Stratifying Tool in ST-Segment Elevation Myocardial Infarction - Ran, Peng; Wei, Xue-biao; Lin, Ying-wen; Li, Guang; Huang, Jie-leng; He, Xu-yu; Yang, Jun-qing; Yu, Dan-qing; Chen, Ji-yan (Frontiers in Cardiovascular Medicine, 2021)
Background: Shock index (heart rate/systolic blood pressure, SI) is a simple scale with prognostic value in patients with ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI). The present study introduces an updated version of SI that includes renal function. Methods: A total of 1,851 consecutive patients with STEMI undergoing PCI were retrospectively included at Cardiac Care Unit in Guangdong Provincial People’s Hospital and divided into two groups according to their admission time: derivation database (from January 2010 to December 2013, n=1145) and validation database (from January 2014 to April 2016, n=706). Shock Index-C (SIC) was calculated as (SI×100)－estimated CCr. Calibration was evaluated using the Hosmer-Lemeshow statistic. The predictive power of SIC was evaluated using receiver operating characteristic (ROC) curve analysis. Results: The predictive value and calibration of SIC for in-hospital death was excellent in derivation (area under the curve [AUC]=0.877, p<0.001; Hosmer-Lemeshow chi-square=3.95, p=0.861) and validation cohort (AUC=0.868, p<0.001; Hosmer-Lemeshow chi-square=5.01, p=0.756). SIC exhibited better predictive power for in-hospital events than SI (AUC: 0.874 vs. 0.759 for death; 0.837 vs. 0.651 for major adverse clinical events [MACEs]; 0.707 vs. 0.577 for contrast-induced acute kidney injury [CI-AKI]; and 0.732 vs. 0.590 for bleeding, all p < 0.001). Cumulative one-year mortality was significantly higher in the upper SIC tertile (log-rank = 131.89, p < 0.001). Conclusion: SIC was an effective predictor of poor prognosis and may have potential as a novel and simple risk stratification tool for patients with STEMI undergoing PCI. Key words: shock index; renal function; ST-segment elevation myocardial infarction; percutaneous coronary intervention; major adverse clinical events.